La enfermedad de nuestro ser querido nos cambió la vida. Cotidiano del cuidador familiar de un adulto mayor con dependencia total - Aurazo Deza, Guadalupe Del Rosario (2017)
The objective of the present investigation was to reveal the daily life of the family caregivers in the care of the dependent elderly, for that it was worked with 12 dependent older adults coming from the locality of Trujillo, who have been taken care of in the Program of PADOMI of the Center of Primary Health Care (CAP) III Metropolitano, we used the criterion of saturation of speeches and certain criteria of selection, to obtain the information the depth interview was carried out according to the methodology of the hermeneutic analysis in the perspective of Martín Heidegger. The present research is a phenomenological qualitative .The findings show that the caregivers' daily life with the elderly is assumed with commitment and responsibility; Perceives pain and desolation by the impotence of being unable to do anything to mitigate suffering; The illness of their relatives change their lives, preventing them from continuing their daily activities; They cling to God and realize that despite what they are going through it is worth fighting on; Feel that family support is determinant in the perception of the burden of elder care and its relief strategies; Caring is staying there until the end, it is gratifying and it is a retribution; Caring for the elderly is a process of transformation and adaptation taking on multiple roles. This entails in the Heideggerian perspective: Daily life, Healing (care), Concern and Occupation, BeingThrowing, Inauthenticity-authenticity, Being-with, Possibility of another entity. This implies that nurses should train caregivers when their relatives are captured from the service, so that in their homes they put into practice what they learn and provide quality care.